2021
DOI: 10.1093/jalm/jfab042
|View full text |Cite
|
Sign up to set email alerts
|

Role of von Willebrand Factor in COVID-19 Associated Coagulopathy

Abstract: Background COVID-19, the disease caused by SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) can present with symptoms ranging from none to severe. Thrombotic events occur in a significant number of patients with COVID-19, especially in critically ill patients. This apparent novel form of coagulopathy is termed COVID-19-associated coagulopathy (CAC), and endothelial derived von Willebrand factor (vWF) may play an important role in its pathogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…Elevated vWF levels, as we also observed in our own cohort, imply activated or damaged endothelium [35]. It would be anticipated that damaged endothelium would result in the release of ultra-large vWF multimers capable of interacting with platelets, leading to platelet activation, microthrombi, and platelet consumption [5]. In accordance, we also found positive correlations between vWF antigen and activity and H-IPF (%) among patients with high on-aspirin platelet reactivity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Elevated vWF levels, as we also observed in our own cohort, imply activated or damaged endothelium [35]. It would be anticipated that damaged endothelium would result in the release of ultra-large vWF multimers capable of interacting with platelets, leading to platelet activation, microthrombi, and platelet consumption [5]. In accordance, we also found positive correlations between vWF antigen and activity and H-IPF (%) among patients with high on-aspirin platelet reactivity.…”
Section: Discussionsupporting
confidence: 89%
“…There is a great body of evidence that COVID-19 significantly affects the coagulation system, contributing to hypercoagulable states and thrombotic events. The reason for such alterations is multifactorial, including the activation of the thrombo-inflammatory cascade and endothelial dysfunction [4,5]. There is a great need to identify novel markers to stratify disease severity and predict the outcome of disease.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 disease caused by the SARS-CoV-2 (CoV-2) virus starts with an early infectious stage, but it may be followed by viral pneumonia and systemic inflammation that could potentially lead to respiratory failure and multiple organ dysfunction [ 122 , 123 , 124 , 125 ]. It is now well established that the COVID-19 is also associated with hypercoagulation and severe thrombotic complications—‘Corona virus-associated coagulopathy’ (CAC) [ 126 , 127 , 128 ]. Several studies have reported incidence of ischemic stroke, deep vein thrombosis, pulmonary thromboembolism, and thrombosis in small brain vessels leading to cerebral microbleeds in 20–30% of COVID-19 patients admitted to the intensive care unit (ICU).…”
Section: Vwf and Covid-19mentioning
confidence: 99%
“…Multiple hematological abnormalities are observed in COVID-19 patients including elevated levels of fibrinogen and D-Dimer in critically ill patients [ 127 , 136 , 137 ]. However, hematological analyses of these patients have also found that VWF levels and activities were elevated five to six folds beyond the upper normal limit [ 128 , 138 ].…”
Section: Vwf and Covid-19mentioning
confidence: 99%
“…There were four types of thrombosis found in patients with COVID-19: pale thrombus, mixed thrombus (arterial and venous thrombosis), red thrombus, and hyaline thrombus (microvascular thrombosis). A hypercoagulable state in the critically ill patients with COVID-19 was found due to the following mechanisms: severe hypofibrinolysis ( 10 ), endothelial dysfunction ( 11 , 12 ), platelet activation ( 12 , 13 ), endothelial-derived von Willebrand factor (vWF) activation ( 14 ), elevated soluble (s) P-selectin ( 13 , 15 ), gene expression ( 13 , 16 ), inflammatory cytokine activation ( 17 , 18 ), and mannose-binding lectin (MBL)-related complement activation ( 19 , 20 ). Serious adverse events, such as thrombosis and thrombocytopenia syndrome, after COVID-19 vaccination are rare ( 21 ) and are associated with a high mortality rate ( 22 ).…”
Section: Introductionmentioning
confidence: 99%